Ability of Circulating Human Hematopoietic Lineage Negative Cells to Support Hematopoiesis. Issue 1 (January 2015) - Peris, Pilar; Roforth, Matthew M.; Nicks, Kristy M.; Fraser, Daniel; Fujita, Koji; Jilka, Robert L.; Khosla, Sundeep; McGregor, Ulrike
Abstract Hematopoietic stem cell (HSC) self‐renewal is regulated by osteoblast and/or endothelial cells within the hematopoietic niche. However, the true identity of the supporting cells and the nature of the secreted factors remain uncertain. We developed a novel mouse model and analyzed whether circulating human peripheral hematopoietic lineage negative/AP+ (lin−/AP+) cells support hematopoiesis in vivo. Thus, immunocompromised (Rag) mice expressing thymidine kinase (Tk) under the control of the 3.6Col1α1 promoter (Tk‐Rag) were treated with ganciclovir, resulting in osteoblast progenitor cell ablation and subsequent loss of hematopoiesis (evaluated by measuring mouse Ter119+ erythroid cells). Following hematopoietic cell depletion, human bone marrow‐derived marrow stromal cells (MSCs) or lin−/AP+ cells were infused into Tk‐Rag mice and compared with saline infusions. Ganciclovir significantly reduced (7.4‐fold) Ter119+ cells in the bone marrow of Tk‐Rag mice compared to saline injections. Infusion of either MSCs or lin−/AP+ cells into ganciclovir‐treated mice resulted in a 3.3‐fold and 2.7‐fold increase (P < 0.01), respectively, in Ter119+ cells compared to mice receiving saline. Relative to lin−/AP− cells, lin−/AP+ cells expressed high levels of mesenchymal, endothelial, and hematopoiesis supporting genes. Thus, human peripheral blood lin−/AP+ cells represent a novel cell type capable of supporting hematopoiesis in a manner comparable to MSCs. J. Cell. Biochem. 116: 58–66, 2015. © 2014 Wiley Periodicals, Inc.